RIMOXCLAMIN: New therapeutic regimen for Hansen’s Disease cure based on effective sensitivity recovery - Marco Andrey Cipriani Frade; Gustavo Sartori Albertino; Filipe Rocha Lima; Natália Aparecida de Paula; Fabiana Aparecida Correa Cinto; Fernanda Cruz Perecin; Andrezza Westin; Wilson Marques Junior; Helena Barbosa Lugão (Brazilian Journal of Infectious Diseases, 2025)
Background: World Health Organization (WHO) has recommended Multidrug Therapy (MDT/WHO) for Hansen’s Disease (HD) since 1982; nevertheless, relapse, antimicrobial resistance, and adverse reactions indicate the need for new therapeutic regimens. We evaluated the efficacy and safety of the new anti-HD regimen RIMOXCLAMIN (Rifampicin, Moxifloxacin, Clarithromycin, and Minocycline) compared with standard Multidrug Therapy provided by WHO (MDT/WHO). Methodology/principal findings: 66 multibacillary HD new cases (46: RIMOXCLAMIN / 20: MDT/WHO) were evaluated between 2015 and 2023. Patients were followed up at least bimonthly by hansenologists for neurological and cutaneous findings and side effects of treatments. Hands/feet tactile sensitivity tests by Semmes Weinstein Monofilaments (SWM) and Physical Disability Grade (PDG) were carried out on the diagnosis, 3rd, 6th, and 12th months. 84.8 % and 80 % of the patients were classified as Borderline-Borderline (BB) in RIMOXCLAMIN and MDT/WHO groups, respectively, with no significant difference between them (p = 0.12). Nerve thickening was reduced by palpation in both groups: in RIMOXCLAMIN, reduction occurred early (65 % to 28 % at 6-months, p = 0.03; 9 % at 12-months, p = 0.03), while in MDT/WHO, it was later (95 % to 40 % at 12-months, p = 0.002). The greatest difference was at 6 months (p < 0.0001). A significant reduction was observed in pain scales on the 3rd month of treatment only with RIMOXCLAMIN; in the end, both groups showed significant reductions in pain scales, being greater in RIMOXCLAMIN group. 0.5 % reduction in the number of abnormal SWM points on the hands compared to baseline, while in the MDT/WHO group, there was an increase of abnormal points of 5.4 %. On the feet, RIMOXCLAMIN showed a reduction of 17.9 %, while in the MDT/WHO, it was 10.3 %. During follow-up, the RIMOXCLAMIN showed a significant decrease in the sum of altered SWM points compared to MDT/WHO (p < 0.05). Only RIMOXCLAMIN improved PDG monitoring. Both groups reported mild adverse effects. Conclusions/significance: The results indicate that RIMOXCLAMIN was superior to MDT/WHO in terms of quick recovery of neurological damage, evidenced by the improvement of symptoms and sensitivity in hands and feet as early as the third month, with a progressive improvement, maintained after the end of treatment, including a reduce of patients with PDG.